Penerapan Customer Relationship Management Penerimaan Siswa Baru Di Era Pandemi Dengan Metode Extreme Programming - Noer Azni Septiani; Cut Rusda Mallinda (LPPM STIKOM Tunas Bangsa, 2023)
MA Al Muzakir is one of the private schools that tries to produce this superior generation, a generation that is resilient in facing the times, balanced in managing the life of the world and the hereafter. Media for registration of new students or students at MA Al Muzakir in processing new student registration data that is already online but has problems, namely in processing filing data, payment transactions and reports on the results of selection of new student admissions which are still separate or manual. So that it does not make it easier for parents or guardians of students in the registration process to complete. Based on the problems with filing, payments and reports at MA Al Muzakir, it is necessary to process payment transaction data and reports on the results of the selection of new admissions at MA Al Muzakir by trying as much as possible to develop the existing system to be more complete and effective by using the application of customer relationship management (CRM) with the Extreme Programming(XP) method. the author hopes that this can be the right solution for problems with new student registration, especially regarding filing, payments and reports, making it easier for MA Muzakir to process payment transaction data and reports on the selection results of new student admissions at MA Al Muzakir online to parents or guardians.